Ceria (La3+, Sr2+)/Carbonates Nanocomposite Electrolytes with High Electrical Conductivity for Low‐Temperature SOFCs. Issue 5 (1st October 2014) - Jaiswal, Nandini; Kumar, Devendra; Parkash, Om; Upadhyay, Shail
<x xml:space="preserve">Abstract</x> A series of ceria‐based nanocomposites consisting of lanthanum and strontium codoped ceria with composition Ce0.89La0.07Sr0.04O1.925 (CL7S4) and eutectic mixture of carbonates Li2CO3‐Na2CO3 (LNCO) have been prepared by mixing nanosize powders of CL7S4 and LNCO. Samples have been characterized using differential thermal analysis, X‐ray diffraction, scanning electron microscopy combined with energy‐dispersive spectroscopy, thermal expansion, and impedance spectroscopy. A sharp increase in ionic conductivity is observed in all the composite specimens corresponding to superionic transition. Sample containing 35 wt% of carbonate shows the maximum conductivity (2.56 × 10−1 S/cm at 500°C) with activation energy of conduction, Ea 0.23 eV.